Pengembangan Media Pembelajaran Diorama Pada Materi Mengenal Bumi Di Sekolah Dasar - Zaenab, Siti; Farhan, Muhammad; Olipia; Akbar, Muhammad; S, Muhammad Ilham; Resa, Asmirinda; Umar (Universitas Sulawesi Barat, 2025)
This study aims to describe the development process of Diorama as an instructional medium for the topic Knowing the Earth in elementary school, as well as to determine its effectiveness in enhancing the quality of learning. This research is a type of Research and Development (R&D) employing the 4D model, which consists of Define, Design, Develop, and Disseminate stages. The developed Diorama is a three-dimensional medium that visually and concretely represents the Earth's structure, its layers, and various natural phenomena. The key characteristics of this medium are its attractive visual presentation, ease of understanding, and interactivity, as students can directly observe and manipulate the objects in the Diorama. The media was tested on fifth-grade elementary school students. Based on the questionnaire results, out of 10 indicators measured using a Likert scale, the average percentage of students who responded “Strongly Agree” and “Agree” exceeded 85%, with the average score for each item above 3.3. Most students reported feeling happier, more active, and better able to understand the material when using the Diorama. Thus, the Diorama has been proven effective in improving understanding, interest, motivation, engagement, and in creating a fun and non-monotonous learning atmosphere. This medium is recommended for use in thematic learning that requires concrete visualizations to support student comprehension.